2012
DOI: 10.1002/j.1532-2149.2011.00030.x
|View full text |Cite
|
Sign up to set email alerts
|

Spinal modulation of nociception by music

Abstract: Numerous studies have demonstrated the capacity of music to modulate pain. However, the neurophysiological mechanisms responsible for this phenomenon remain unknown. In order to assess the involvement of descending modulatory mechanisms in the modulation of pain by music, we evaluated the effects of musical excerpts conveying different emotions (pleasant-stimulating, pleasant-relaxing, unpleasant-stimulating) on the spinally mediated nociceptive flexion reflex (or RIII), as well as on pain ratings and skin con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 29 publications
1
35
0
4
Order By: Relevance
“…The non-musical sound samples consisted of alternating, frequency-filtered noise clips that were chosen based on studies where participants perceived filtered noise to be less distressing than white noise [33], [34]. During Session 2, all participants chose the song they wanted to listen to during the pain trials prior to their first exposure to audio.…”
Section: Methodsmentioning
confidence: 99%
“…The non-musical sound samples consisted of alternating, frequency-filtered noise clips that were chosen based on studies where participants perceived filtered noise to be less distressing than white noise [33], [34]. During Session 2, all participants chose the song they wanted to listen to during the pain trials prior to their first exposure to audio.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, numerous studies have experimentally demonstrated the benefits of induced PA on acute pain, with the general finding that PA inductions reduce pain sensitivity (See Table 1 for a selection of studies across nociceptive stimulus and affective induction modalities). Such effects have been observed in studies involving positive affective induction through the viewing of emotionally evocative images (e.g., 29;30;31;32;33;34;35;36), humorous film clips (37;38), romantic film clips (39), therapeutic suggestion (40), hypnotic suggestion (41), guided imagery (42), laughter (43), pleasant odors (44;45), pleasant music (35;4650), and monetary reward (51). Recent work using the nociception flexion reflex design suggests that the effects of induced PA on pain may be spinally mediated (32;33;52).…”
Section: The Influence Of Pa Relative To Na In the Experience Of Painmentioning
confidence: 99%
“…Studien zeigten, als "unschön" empfundene Musik die Aktivität der Nozizeptoren sowie die Reflexantwort auf einen Schmerzreiz eher verstärkt. [59] Nur die favorisierte, als "schön" empfundene Musik bewirkt hier einen lindernden Effekt. Unter fMRT-Kontrolle konnte gezeigt werden, dass eine als besonders angenehm empfundene Musik die neuronale Aktivität im Gyrus cinguli hemmt und die Schmerz-Perzeption deutlich verändert [24].…”
Section: Der Schmerz In Der Musikgeschichteunclassified